Voice Assistant Using Python - Saxena, Anuj (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2023)
Today, technological innovation is accelerating. Previously, we could only perform a few things on a computer system. However, machine learning, artificial intelligence, deep learning, and a few other technologies have advanced computer systems to the point where we can accomplish any work. If individuals are still trying to communicate utilising numerous input devices in this day and age, it's not worth it. As a result, we created a voice assistant in Python that allows the user to run any type of command in Linux without using the keyboard. The primary function of a voice assistant is to reduce the use of input devices such as a keyboard, mouse, and so on. It will also save hardware space and money.